PENERAPAN GOOD GOVERNANCE DI TINJAU DARI TRANSPARANSI PEMERINTAH DALAM PENGADAAN BARANG DAN JASA RUMAH SAKIT UMUM DAERAH MELALUI PROSES TENDER DI KABUPATE MANDAILING NATAL - Sari, Yulanna; Aisyah, Dara (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Good Governance is a fundamental aspect in building government governance that is oriented towards the principles of integrity, transparency, accountability, effectiveness, and responsiveness to public interests. Good Governance includes several main principles, including transparency, accountability, participation, the rule of law, effectiveness, efficiency, and justice. This study aims to analyze the application of Good Governance principles reviewed from the aspect of government transparency in the procurement process of goods and services in the tender for the construction of the Regional General Hospital in Mandailing Natal Regency. The background of this study is based on the still low level of public information disclosure in the implementation of the tender, which causes project failure, construction delays, and disruptions to the Electronic Procurement Service (LPSE) system. The research method used is a descriptive method with a qualitative approach.. Data were collected through interviews, field observations, documentation, and literature studies relevant to the goods and services procurement process. The research informants consisted of the Head of the Goods and Services Division, the Head of the Development and Advocacy Division, implementing staff, and representatives of local media. The results of the study indicate that the implementation of Good Governance principles in the procurement of goods and services in Mandailing Natal Regency has not been running optimally. This study emphasizes the importance of implementing the principles of transparency and accountability in the public procurement system to create good, clean, and community-oriented governance.